PENERAPAN PEMBELAJARAN BERBANTUAN TEKNIK ICE BREAKING PADA MATA KULIAH ALJABAR LINEAR TERHADAP HASIL BELAJAR MAHASISWA - Suryati, Kadek; Setiawan, I Made Dedy (PendIPA Journal of Science Education, 2024)
The purpose of this study was to determine the effect of the application of ice breaking technique-assisted learning on linear algebra courses. This type of research was a quasi-experimental research. The subjects of this study were second-semester computer systems engineering students. The research sample technique was taken using the random sampling method. The sample was divided into one experimental class and one control class. For the experimental class, learning with ice breaking techniques will be given and for the control group with conventional learning. By implementing three stages, namely the preparation stage, the implementation stage and the final stage. The data collection method used is documentation and test methods. The types of data collected are primary and secondary data. For the data analysis method, it will be carried out with the help of the SPSS program using the t-test. From the results of the research and data analysis, the test statistic value was obtained as 2.8820 with a significance value of 0.0071 with a significance level of 0.05, indicating that there is an effect of the application of ice breaking technique-assisted learning on student learning outcomes.